2018
DOI: 10.1075/dujal.18006.sta
|View full text |Cite
|
Sign up to set email alerts
|

The influence of L2 English on L3 French acquisition in bilingual education*

Abstract: In the present paper, we compare L2 English influence on French third language acquisition (L3A) in first-year and third-year bilingual stream secondary school students and in third-year mainstream secondary school students by means of a gap-filling task. We found that the influence of L2 English on French L3A increases from first- to third-year bilingual students, which is not the case in the mainstream group. This raises the question if L2 influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Note that we did find an increase of Adv-V errors from year 1 to year 3 in the guided production task(Stadt et al 2018b). …”
mentioning
confidence: 52%
“…Note that we did find an increase of Adv-V errors from year 1 to year 3 in the guided production task(Stadt et al 2018b). …”
mentioning
confidence: 52%
“…In such a program, the quantity of exposure to English as a foreign lan-guage is very high as compared to the exposure to French. In this population of language learners, Stadt et al (2018) found crosslinguistic influences from both Dutch and English to French and that exposure to English affects crosslinguistic influence from English to French. Based on these findings, French may be taken as a third language (L3) in Dutch-English bilingual education, while English may be taken as an L2.…”
Section: Introductionmentioning
confidence: 77%
“…Within such a context, transfer has been defined as a psychological process in which L2 learners incorporate L1 features into the L2 (Kellerman 1977). Recent studies on transfer showed that foreign languages such as French, are not always L2's in secondary education (Stadt et al 2018;Stadt 2019). These studies focused on Dutch learners of French who were enrolled in a Dutch-English bilingual program.…”
Section: Introductionmentioning
confidence: 99%
“…In our study it is not the acquisition of morphology, syntax, or semantics, but of pragmatics where we see this effect. Because English is also the L2 for Dutchspeaking learners of Spanish (Stadt et al 2018), we cannot exclude the possibility that the Dutch data are also the result of L2 influence rather than L1 influence, or both (Bohnacker 2021). Stadt et al (2018) argue that the influence of English L2 on the acquisition of L3 is dependent on the degree of exposure to the L2, rather than on L2 proficiency.…”
Section: English L2 Interference In Spanish L3 Acquisitionmentioning
confidence: 99%
“…The influence of English as an L2 on the acquisition of an L3 is wellestablished (see e.g., Stadt et al 2018, Westergaard 2021. Hammarberg (2001) points out that there is in fact a general tendency to activate an earlier L2 rather than the L1 in L3 performance.…”
Section: English L2 Interference In Spanish L3 Acquisitionmentioning
confidence: 99%